The Influence of Printing Speed and Temperature on the Mechanical, Absorptive, and Morphological Properties of PLA-Based Hybrid Materials Produced with an FDM-Type 3D Printer - İncesu, Rumeysa; Akderya, Tarkan (Polymers, 2024)
Composite materials are used in many engineering applications and industrial fields due to their superior properties, such as high strength, lightweight, and stiffness. These outstanding properties have made these materials an alternative to metallic materials. The vital need for new lightweight and inexpensive materials with superior strength properties has led to research on “hybridisation”. Hybrid composites with more than one type of polymer in the same structure are needed to achieve a better balance of properties and to combine many desired properties in a single material. Many researchers have studied the hybrid effect and contributed to the understanding and modelling of the subject. Studies to explain the primary mechanism of the hybrid effect are limited and insufficient to explain the complex interaction. In this study, a three-dimensional printer using fused deposition modelling technique was used to produce hybrid materials, and the influence of printing parameters on the mechanical, absorptive, and morphological properties of poly (lactic acid) (PLA), Tough PLA, and PLA/Tough PLA hybrid materials were investigated. The hybrid material form exhibited superior properties when selecting specific production parameters from individual raw elements. It can be said that the mechanical properties of the PLA/Tough PLA hybrid material increased with the increase in production temperature.